CHAQ2020 - Seymour Island - Spatial data - CHAQ2020 - Seymour Island - Raw data ... : CHAQ2020 - Seymourön - Spatiala data - CHAQ2020 - Seymourön - Rådata ... - Westin, Jonathan; Almevik, Gunnar (University of Gothenburg, 2021)
The first Swedish Antarctic Expedition (1901-1903), led by Otto Nordenskjöld, sailed to Antarctica on the ship Antarctic captained by CA Larsen, and established a research station on Snow Hill Island. There six members overwintered and performed paleontological, meteorological, geomagnetic and geological studies, while the rest of the expedition set sail for South Orkney. After the winter, on the way back to Snow Hill Island, the Antarctic got stuck in the ice and sank. At this point, the expedition members were divided into three groups. One of these overwintered an extra year on Snow Hill Island, whereas the other two groups were forced to build stone huts in order to overwinter at Hope Bay and Paulet Island. An Argentinean vessel, the Corbeta Uruguay, rescued the expedition in November 1903. CHAQ 2020 is an Argentinean-Swedish project with fieldwork in the area around the Antarctic Peninsula aiming to investigating and documenting the historical remains of the first Swedish South Polar expedition under ... : Syftet med forskningsprojektet var att dokumentera lämningarna efter Otto Nordenskjölds Antarktisexpeditionen 1901-1903. Materialet består av fotografier, planer, ritningar, 3d-modeller och drönarfilmer från Snow Hillön, Hoppets vik och Seymourön. Denna katalogpost samlar den spatiala datan från Seymourön, vilket inkluderar punktmoln och texturerade trådmodeller skapade genom structure-from-motion fotografering. Se den engelska beskrivningen för mer information. Detta dataset samlar de fyra fotoset som structure-from-motion-modellerna av monumenten är uppbyggda med. Fotografierna togs med en Fujifilm X-T2 den 4-6 januari 2020. Lämningarna av båten var sköra och därför svåra att infånga på ett sätt som förhindrade morfologiska förändringar mellan dokumentationen av de båda sidorna. Fotografierna togs av Gunnar Almevik. ...